Penyuluhan Tentang Pembuatan Teh Daun Binahong (Anredera Cordifolia (Ten) Steenis), Sebagai Pengobatan Asam Urat Di SMAN 07 Kota Bengkulu: Conseling On Making Binahong Tea (Anredera Cordifolia (Ten) Steenis), Ad A Treatment For Gout At SMAN 07 Bengkulu City - Lestari, Gina; Yuska Noviyanty; Gheryn Widian; Fitri Chaniago; Kenli Puspita Dea; Ulfa Sri Julia (Bengkulu Institute, 2023)
Binahong leaves (Anredera cardifolia (Ten) Steenis) or also known as madeira vine leaveshave anti-inflammatory, antioxidant, antibacterial and anti-pain properties which areimportant for body health. These properties are supported by the various natural compoundscontained in it, including flavonoids, saponins, and tannins. The purpose of this study was todetermine the effectiveness of binahong leaf tea in reducing uric acid levels. The activitiescarried out include counseling on the health of the human body for the community andstudents. This activity is expected to provide benefits for students and the community inincreasing knowledge and understanding of the important properties of tea from binahongleaves (Anredera cordifolia (Ten) Steenis)